2000
DOI: 10.1108/00368790010308401
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of wear mechanism of duplex treated M7 HSS drill bits

Abstract: The surface coating of drill bits improves the tool life considerably and enhances the end product quality. The improved coating is desirable for long service operations. One of the methods to achieve this is to develop an interface layer between the coat and the tool base such that the transition of shear properties occurs across the interface layer. The application of duplex treatment (plasma pre‐nitriding before PVD TiN coating) to the tool surface becomes fruitful in this regard. In the present study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It has been observed that in HSM ball-nose end milling of H13, the cutting temperature increases with an increase of cutting speed and depth of cut [14]. The increased oxidation stability of TiAlN layers with a high content of aluminium leads to an improvement in abrasion resistance and wear of the tool [15]. The superiority of TiAlN to TiN has been attributed to better oxidation resistance [16].…”
Section: Results On Surface Roughness Of H13 Tool Steelmentioning
confidence: 99%
“…It has been observed that in HSM ball-nose end milling of H13, the cutting temperature increases with an increase of cutting speed and depth of cut [14]. The increased oxidation stability of TiAlN layers with a high content of aluminium leads to an improvement in abrasion resistance and wear of the tool [15]. The superiority of TiAlN to TiN has been attributed to better oxidation resistance [16].…”
Section: Results On Surface Roughness Of H13 Tool Steelmentioning
confidence: 99%
“…The Laplace inversion of boundary conditions gives Tðx; 0Þ ¼ 0 and vTðx; pÞ vx x¼0 ¼ rVL kp [5] and TðN; pÞ ¼ 0 [6] The analytical solution to eqn [4] gives the result: The Laplace inversion of boundary conditions gives Tðx; 0Þ ¼ 0 and vTðx; pÞ vx x¼0 ¼ rVL kp [5] and TðN; pÞ ¼ 0 [6] The analytical solution to eqn [4] gives the result:…”
Section: Heating Analysismentioning
confidence: 99%